Language development deficits and early interactive music intervention (BusyBaby): protocol description of a double-blind randomized controlled trial on the effectiveness of music on language development in infancy - Virtala, P.; Aquilino, B.; Nie, P.; Navarrete-Arroyo, S.; Stolt, S.; Leutonen, K.; Lauronen, M.; Kujala, T. (Frontiers in Psychology, 2026)
BackgroundInfancy and early childhood lay the foundation for language and reading abilities. They are crucial for success in social relationships, education, and work life, but can be compromised by heritable conditions such as developmental dyslexia. Music activities have shown associations with auditory, language, and literacy skills, but randomized controlled trials (RCTs) have been lacking, especially in young and at-risk populations. This two-arm RCT evaluates the efficacy of an early music intervention for language development. As highly novel aspects, we investigate whether and how the efficacy is influenced by familial dyslexia risk and its genetic markers, as well as intervention timing (children’s age and developmental status), and mediated by expected social–emotional benefits of the interventions on the parent, child, and their interaction.MethodsA maximum of 200 infants will be recruited for the trial, with approximately 50% of them at familial dyslexia risk, and randomized to the experimental (music intervention) or control arm (circus intervention), where they will start a weekly 6-month intervention at the age of approximately 8–12 months. Outcome measures will be evaluated at baseline, at 6 months (after the intervention), and at a 1-year follow-up (1.5 years from the baseline). As primary outcome measures of language development, language abilities will be evaluated with standardized parental questionnaires (validated parental report instruments) and neural speech processing with auditory event-related potentials. Further outcome measures include, for example, standardized tests of language development, standardized parental questionnaires on social–emotional factors, neural processing of music, questionnaires and standardized tests of motor development, and dyslexia genetics (DNA sampling).DiscussionThe present trial is expected to fill significant gaps in previous research on the effects of early-age musical activities on language development. By comparing a musical intervention to an equally active, social, structured, and pleasurable circus intervention in a randomized, controlled setting with pre- and post-assessments, the unique benefits of musical activities can be probed reliably. The trial can provide completely novel information on the moderators and mediators of the intervention outcomes, including participant characteristics such as dyslexia risk, age, and developmental stage, as well as social–emotional benefits of pleasurable group activities.Clinical trial registrationClinicalTrials.gov; identifier NCT06261307.